2006
DOI: 10.1080/10803548.2006.11076701
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Workers’ Exposure to Methylene Diphenyl Diisocyanate (MDI) in an Automobile Manufacturing Company, Iran

Abstract: Evaluation of personal inhalation exposure to methylene diphenyl diisocyanate (MDI) among

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Whereas Maitre et al (1993) have measured a value of 12 μmol/mol creatinine for HDI exposure at the same concentration from a separate survey of workers. In a developing country, the above situations reinforced the reasons why Kakooei et al (2006) had expressed the importance of studying indoor air pollution in such industries. For the imported technology and the machinery used without suitable application of adequate engineering controls and proper safe work practice together with the levels of training and awareness can cause great exposure to air pollutants and may result in more occupational health problems than in the developed countries.…”
Section: Hdi and Hda Relationship In The Factoriesmentioning
confidence: 99%
“…Whereas Maitre et al (1993) have measured a value of 12 μmol/mol creatinine for HDI exposure at the same concentration from a separate survey of workers. In a developing country, the above situations reinforced the reasons why Kakooei et al (2006) had expressed the importance of studying indoor air pollution in such industries. For the imported technology and the machinery used without suitable application of adequate engineering controls and proper safe work practice together with the levels of training and awareness can cause great exposure to air pollutants and may result in more occupational health problems than in the developed countries.…”
Section: Hdi and Hda Relationship In The Factoriesmentioning
confidence: 99%
“…However, occupational exposure to NCO is often a mixture of monomers and oligomers so there is some uncertainty in the comparison of the results of the biological control of exposure (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) . Biological markers have relatively short half-lives in urine, 2-5 hours, which means that urine samples must be collected at the end of exposure and results mainly reflect exposure on the day of collection (14) , halflives in plasma are usually longer (20-25 days), Sabbioni et al have shown that methylenediphenyl diisocyanate (MDI) forms adducts with lysine in plasma albumin and may offer a potential for assessing risk (16)(17) . All the volunteer studies and occupational studies with both air and biological monitoring show good correlations between exposure, mostly inhalation, and levels of biomarkers in urine or blood and advocate the usefulness of biological monitoring.…”
Section: Introductionmentioning
confidence: 99%